Synthesis and characterization of thin film nanocomposite forward osmosis membrane with hydrophilic nanocomposite support to reduce internal concentration polarization - Emadzadeh, D. (Elsevier, 2014)
Realizing that one of the most important challenges in the forward osmosis (FO) membrane is internal concentration polarization (ICP), thin film nanocomposite (TFN) membranes were prepared by incorporating different loadings of titanium dioxide (TiO2) nanoparticles (ranging from 0 to 0.90 wt%) into the polysulfone (PSI) substrate in order to reduce ICP. The nanocomposite substrates prepared were characterized with respect to hyclrophilicity, overall porosity, surface roughness and cross-sectional morphology by different methods. Results revealed that both hydrophilicity and porosity of the substrate were increased upon addition of TiO2 nanoparticles. Moreover, a large number of finger-like macrovoids were developed by increasing the loading of TiO2 nanoparticles, leading to enhancement in water permeability. As for the FO performance tested at AL-FS orientation and with Dl water as feed and 0.5 M NaCl as draw solution, the TFN membrane prepared using PSI substrate embedded with 0.60 wt% TiO2 nanoparticles (designated as TFN0.60) exhibited the most promising result by showing water flux of 18.81 L/m(2) h, Le. 97% higher than the control TFC membrane prepared by substrate without TiO2 incorporation (designated as TFC), with no significant change in reverse solute flux. Compared to the control TFC membrane, the FO water flux of TFN0.60 was also reported to increase significantly from 4.2 to 8.1 L/m(2) h (AL-FS orientation) and from 6.9 to 13.8 L/m(2)h (AL-DS orientation) when seawater was used as feed solution and 2 M NaCl was used as draw solution. The increase in water flux can be attributed W the decrease in structural parameter (S value = 0.39 mm), mainly due to the formation of finger-liked macrovoids that connect the Lop and bottom layer of the substrate and reduce the tortuosity, resulting in decreased ICP. Although further increasing TiO2 nanoparticles loading to 0.90 wt% could increase membrane water permeability, the FO performance was compromised by a significant increase in reverse solute flux. To the best knowledge of the authors, this is the first report on TFN membrane using PSf-TiO2 nanocomposite substrate for FO applications.